2013
DOI: 10.1002/cncr.27795
|View full text |Cite
|
Sign up to set email alerts
|

Survival after lumpectomy and mastectomy for early stage invasive breast cancer

Abstract: Background Randomized clinical trials (RCT) have demonstrated equivalent survival for breast conserving therapy with radiation (BCT) and mastectomy for early stage breast cancer. We studied a large, population-based series of women who underwent BCT or M to observe whether outcomes of RCT were achieved in the general population, and whether survival differed by surgery type when stratified by age and hormone receptor (HR) status. Methods We obtained information regarding all women diagnosed in the state of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
168
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(188 citation statements)
references
References 19 publications
13
168
2
5
Order By: Relevance
“…Previous SEER studies have compared 2 treatments at a time: some reported a survival advantage with bilateral vs unilateral mastectomy 21,22 and others reported improved survival after breast-conserving surgery with radiation compared with unilateral mastectomy. 23,24 By comparing all 3 surgical options for a patient with early-stage breast cancer, we found no mortality benefit associated with bilateral mastectomy compared with breast-conserving surgery, and higher mortality associated uniquely with unilateral mastectomy.…”
Section: Discussionmentioning
confidence: 86%
“…Previous SEER studies have compared 2 treatments at a time: some reported a survival advantage with bilateral vs unilateral mastectomy 21,22 and others reported improved survival after breast-conserving surgery with radiation compared with unilateral mastectomy. 23,24 By comparing all 3 surgical options for a patient with early-stage breast cancer, we found no mortality benefit associated with bilateral mastectomy compared with breast-conserving surgery, and higher mortality associated uniquely with unilateral mastectomy.…”
Section: Discussionmentioning
confidence: 86%
“…Some authors found lower mastectomy rates in oBCP [2,5] whilst others found it increased [1,20,22,35] including larger epidemiological studies [36,37]. An informed consent has been shown to increase the compliance and patient satisfaction [38].…”
Section: Surgical Treatmentmentioning
confidence: 96%
“…Breast-conserving therapy consisting of BCS with radiotherapy has become the standard of care for early-stage breast cancer because of equivalent local control and survival for both BCT and mastectomy. Moreover, according to a recent report, BCT was associated with improvement in overall survival and diseasespecific survival regardless of age or hormone receptor status [33]. Although EBCTCG data demonstrated that omission of radiotherapy was one of the most relevant factors associated with local recurrence and the relationship between effects on local control and breast cancer mortality showed that 1 death from breast cancer could be avoided for every 4 local recurrences prevented [3,4], 20% of patients who underwent BCS in Japan did not receive WBI [34] because they had complete pathologically negative margins, occasional severe adverse events because of WBI, and long-term daily visits to radiation institutes.…”
Section: Discussionmentioning
confidence: 98%